What's better than the asynchronous discussion post? (Journal of Applied Learning and Teaching, 2022)
The “discussion post” has been a staple in higher education online classrooms for decades. While educators of online learning widely rely on asynchronous discussion posting to engage students using institutional learning management systems (LMS), discussion posting requires mediation and motivation to sustain participation, is considered task-oriented by students, and has been frequently criticized for inauthentic dialogue. The Slides Strategy, which utilizes a collaborative Google Slide deck in concert with Parallaxic Praxis, a knowledge-generating framework, creates an effective environment for meaningful engagement – demonstrating student understanding of material, creating classroom community, and provoking rich, critical dialogue. Collaborative slides used as a pedagogical tool in this way encourage value of all perspectives, diverse modality and thought, and inclusivity through a platform that allows different literacies to cohabitate, working toward decolonizing academia. This paper contextualizes reflections from five asynchronous online courses taught by different instructors, and provides evidence assessing the effectiveness of this strategy through instructor and student perspectives. As educational institutions continue to grapple with an increasing reliance on, and need for, innovative, dynamic, and supportive online learning environments in a post-pandemic landscape, the Slides Strategy moves the online discussion post to a more authentic and critically reflexive academic conversation.